2022
DOI: 10.3389/fendo.2022.900121
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nomograms to Predict Delayed Hyponatremia After Transsphenoidal Surgery for Pituitary Adenoma

Abstract: ObjectiveThis study aimed to develop a nomogram of clinical variables and magnetic resonance imaging scans to predict delayed hyponatremia after transsphenoidal surgery for pituitary adenoma.MethodsPatients who underwent transsphenoidal surgery for pituitary adenoma in Fuzong Clinical Medical College of Fujian Medical University between January 2012 and December 2020 were retrospectively investigated. Medical records, MRI findings, and laboratory examination results were recorded as candidate variable predicto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…The incidence rate of PDH varies widely among publications, ranging from 2 to 35% [ 1 , 6 ]. One possible explanation for the wide range of incidence rates among different publications is the inconsistence in the diagnostic criteria used for PDH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence rate of PDH varies widely among publications, ranging from 2 to 35% [ 1 , 6 ]. One possible explanation for the wide range of incidence rates among different publications is the inconsistence in the diagnostic criteria used for PDH.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has reported various predictors for PDH, including old age, serum sodium concentrations on postoperative days (POD) 1 and 2 [ 2 5 ], postoperative diabetes insipidus, diaphragma sellae sinking depth, and postoperative length of the “measurable pituitary stalk” [ 6 ]. However, the relation between tumor type, tumor size, and PDH has not reached a consistent conclusion [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon admission, all patients undergo radiological examination to observe tumor location and its relationship with surrounding tissues, classi ed into Knosp grades 0-4 [9] . The angle of deviation of the pituitary stalk is recorded on T1 + C scans, de ned as the angle at which the pituitary stalk deviates from the midline at its point of origin [10] (Fig. 1).…”
Section: Diagnostic Criteria and De Nitionsmentioning
confidence: 99%
“…Pituitary adenomas constitute 10–15% of intracranial tumors and are the most prevalent sellar lesion [ 1 ]. The primary treatment for pituitary adenomas is transnasal sphenoid surgery, which has a low incidence of complications [ 2 ].…”
Section: Introductionmentioning
confidence: 99%